2023
DOI: 10.3389/fpubh.2023.1221501
|View full text |Cite
|
Sign up to set email alerts
|

The mediation effect analysis of nurse’s mental health status and burnout under COVID-19 epidemic

Fuzhi Liu,
Yanyan Zhao,
Yangjia Chen
et al.

Abstract: AimThe objective of this study is to investigate the mental health status of nurses during the outbreak of novel coronavirus pneumonia. Additionally, we aim to analyze the relationship between anxiety, depression, and burnout among nurses. The findings will provide a scientific basis for promoting the psychological health of nurses.MethodsUsing a cross-sectional study, nurses in Quanzhou in May 2020 completed a general information questionnaire, the 7-item Generalized Anxiety Disorder Questionnaire (GAD-7), Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 73 publications
(74 reference statements)
0
1
0
Order By: Relevance
“…In various systematic reviews and meta-analyses, healthcare professionals have reported significant mental health issues, including elevated levels of anxiety and depression. The study discovered higher levels of anxiety(4.23±4.43) and depression(5.47±5.42) compared to previous outcomes(anxiety:4.10±4.34; depression:5.09±5.62) of the analogous study [48]. One possible explanation for this phenomenon could be the notable surge in COVID-19 cases within the…”
Section: Discussionmentioning
confidence: 50%
“…In various systematic reviews and meta-analyses, healthcare professionals have reported significant mental health issues, including elevated levels of anxiety and depression. The study discovered higher levels of anxiety(4.23±4.43) and depression(5.47±5.42) compared to previous outcomes(anxiety:4.10±4.34; depression:5.09±5.62) of the analogous study [48]. One possible explanation for this phenomenon could be the notable surge in COVID-19 cases within the…”
Section: Discussionmentioning
confidence: 50%